RADIOLOGICAL DIAGNOSTIC OF PLACENTA ACCRETE IN PREGNANT WOMEN WITH CESAREAN SCAR - A. V. POMORTSEV; E. D. KHUDOROZHKOVA; M. A. MATOSYAN; V. V. MAKUKHINA; I. G. NOSULYA (Кубанский научный медицинский вестник, 2018)
Aim. To define significant ultrasound and magnetic resonance imaging markers in diagnostics of the depth of chorion invasion in myometrium in pregnant women after Cesarean section was carried out.Materials and methods. 68 pregnant women from 28 to 32 gestation weeks with Caesarian scar and placenta on the front wall of uterus were retrospectively studied. Pregnant women were divided into 4 groups depending on histologic verification of placenta invasion depth. MRI and ultrasound assessment of the lower uterine segment was carried out and the most significant US and MRI markers of placenta accreta were distinguished. Subsequently, the received results of the research were processed by algorithms of factor analysis with calculation of informativeness of each marker and with determination of the forecast of placenta accreta.Results. As a result, group I of pregnant women scored within 0-0.9 conventional units, in group II – 1-3 conventional units, in group III – the score was 3.1-5.0 conventional units, in group IV – 5.1-7.0 conventional units. In groups III and IV are characterized by the fact of signs combination. In group III the combination of 2 signs was detected in 65% of cases, of 3 signs – in 25% of pregnant women.Conclusion. The most informative marker of ultrasound diagnostic of placenta accreta was determination of venous lacunas in its suprabasal part (0.42), in case of MRI it was the assessment of the bladder wall (0.45). The sensitivity and specificity of ultrasonography were 86.2% and 84.8%, in MRI they were 96% and 94.4% respectively.